The Effect Of Entrepreneurial Characteristics And Creativity On The Success Of Small And Medium-Sized Food Businesses - Fadhel Alfarozi Herey; Ahmad Soleh; Ida Ayu Made Er Meytha Gayatri (Utami Publisher, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play an important role in promoting economic growth in Bengkulu Selatan Regency by improving community welfare and creating job opportunities. However, not all culinary MSMEs are able to survive in an increasingly competitive market. This study aims to analyze the effect of entrepreneurial characteristics and creativity on the success of culinary MSMEs, both partially and simultaneously. The population of this study consisted of 462 culinary business actors, with data collected through questionnaires and analyzed using multiple linear regression, validity and reliability tests, t-test, F-test, and the coefficient of determination. The regression equation obtained is Y = 50,600 – 0,766X1 + 0,783X2 + 2.945, showing that the entrepreneurial characteristic variable (X₁) has a negative and significant effect on business success with a significance value 0.000, while the creativity variable (X₂) has a positive and significant effect with a significance value 0.000. These findings indicate that creativity has a more dominant influence in improving the success of culinary MSMEs in Bengkulu Selatan Regency.